Customer satisfaction toward PPK services in Muda Authority Development Area (MADA) - Romzan, Norhaniza (2016)
Small-scale farmers still predominate and the majority of them are engaged in growing paddy. On 2011, statistics shows that there are 177,230 paddy farmers in Malaysia. However, only 40% are working as full-time farmers. In Peninsular Malaysia, Kedah has the highest number of paddy farmers which are 31,820 farmers. Malaysia paddy areas are divided by two granaries which are major and minor granary area. Muda area, Kedah-Perlis is one of the major granary areas under responsibility of Muda Agriculture Development Authority (MADA) and Area Farmer’s Organization (PPK). PPK is one of organization under MADA are responsible to manage, coordinate and provides the facilities to farmers. Eight (8) services are offered by PPK for farmers which are management and development of human resources, farm mechanization, farm infrastructure, providing farm input, fund and saving, extension and advices, harvesting technology, food processing technology, marketing, and farm cyber center. Satisfactions of farmers towards PPK service are very important in order to help the farmers to improve their production and yields of rice for nation. However, there are a few problems facing by PPK in their services which are: their service quality is low, farmers has low confident toward PPK and communication problem among farmers and PPK. This study was conducted to examine the service quality of PPK in Muda area. The specific objectives are to determine respondents’ satisfaction level toward PPK services and to examine the relationship between socio demographic factors with satisfaction level toward PPK services. Questionnaire form was designed before distributed to 200 respondents from four (4) regional of PPK at Muda area. Data will analyze by using Statistical Package for the Social Science (SPSS) version 21.0. Three (3) types of statistics analysis techniques were used to analyze the data which are descriptive, chi-square and gap analysis. As a result, we found that perception level of respondents toward PPK services is moderate and there are significant relationship between socio demographic factors and perception level toward PPK services. As conclusion, farmer’s expectation towards PPK is always high since everybody always want the best but the performance of PPK are at medium level and a lot of improvement need to be done. There is also a few recommendations that should be done in future studies to improve this study which are PPK must make improvement on the three (3) most expected services which are advices and agriculture extension, management and human resources development, PPK board director.